2017
DOI: 10.1128/aac.00604-17
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Plectasin NZ2114 from a Hybrid Silicone-Hydrogel Material for Inhibition of Staphylococcus aureus Biofilm

Abstract: Staphylococcus aureus is a major human pathogen in catheter-related infections. Modifying catheter material with interpenetrating polymer networks is a novel material technology that allows for impregnation with drugs and subsequent controlled release. Here, we evaluated the potential for combining this system with plectasin derivate NZ2114 in an attempt to design an S. aureus biofilm-resistant catheter. The material demonstrated promising antibiofilm properties, including properties against methicillin-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Due to limitations in the manufacturing process, the IPN concepts explored in the latter are often microscale particle based. As we recently showed, IPN can, however, also be manufactured as a non-degradable base material in flexible medical devices, providing a reservoir in the bulk of the material for controlled release of drugs (Stenger et al, 2016;Klein et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to limitations in the manufacturing process, the IPN concepts explored in the latter are often microscale particle based. As we recently showed, IPN can, however, also be manufactured as a non-degradable base material in flexible medical devices, providing a reservoir in the bulk of the material for controlled release of drugs (Stenger et al, 2016;Klein et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They have been explored over the past 80 years as components in drug carrier systems and found use in microscale capsule-based formulations and biodegradable implants that enable site-specific controlled drug delivery (Changez et al, 2004(Changez et al, , 2005Lohani et al, 2014;Aminabhavi et al, 2015). Recently, we showed that IPNs could also successfully be incorporated into silicone-based medical devices, essentially converting the device bulk material into a drug reservoir while maintaining device functionality (Stenger et al, 2016;Klein et al, 2017). This provides a conceptual alternative solution to the current challenges of designing anti-infective coatings (Myung et al, 2008;Stenger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[109][110][111] While commercial development was halted, preclinical studies are actively ongoing with promising results. [112][113][114][115][116] Oragenics (Tampa, FL, USA) has investigated…”
Section: Systemic Antibioticsmentioning
confidence: 99%
“…Human defensin peptides themselves are unlikely to be developed into therapeutics because of their well-described functional versatility 115119. A derivative of the fungal defensin plectasin, termed NZ2114, has shown most promise to date, with in vivo efficacy in infectious models as well as applications to combat biofilm formation 120122. Similar to the plectasin study, we identified C-terminal hydrophobic residues Ile20 and Leu25 of Human Neutrophil Peptide-1 to be mainly involved in Lipid II binding.…”
Section: Introductionmentioning
confidence: 99%